Effect of relaxation on stress, anxiety and depression level of the caregivers' of cancer patients (Dhaka University Journal of Biological Sciences, 2017)
The study was carried out to explore the outcome of relaxation on stress, anxiety and depression level of the caregivers of cancer patients. Fifty caregivers of cancer survivors were randomly assigned to two groups. In intervention group, participants received relaxation once a week for five consecutive weeks while control group received no intervention. Stress (life‐stress questionnaire), anxiety (anxiety scale) and depression (depression scale) levels were assessed before and after the intervention. Data were analyzed by independent sample t test. Results showed that relaxation helped the caregivers of cancer patients to reduce their stress and anxiety. But relaxation did not reduce the level of depression. Implication of the research and future guideline are also discussed.Dhaka Univ. J. Biol. Sci. 26(2): 151-158, 2017 (July)